Audio-Visual Spatiotemporal Perceptual Training Enhances the P300 Component in Healthy Older Adults - Yang, Weiping; Guo, Ao; Li, Yueying; Qiu, Jiajing; Li, Shengnan; Yin, Shufei; Chen, Jianxin; Ren, Yanna (Frontiers in Psychology, 2018)
The cognitive abilities of older adults, such as those associated with vision and hearing, generally decrease with age. Several studies have reported that audio-visual perceptual training can improve the perceived competence to visual and auditory stimuli, suggesting that perceptual training is effective and beneficial. However, whether audio-visual perceptual training can induce far-transfer effects in older adults remains unclear. In this study, the classic P300 component, which is regarded as a neurophysiological indicator of cognitive processing of a stimulus, was selected as an evaluation index of the training effect in this study. We trained both young and older adults on the ability to judge the temporal and spatial consistency of visual and auditory stimuli. The results showed that the P300 amplitudes were significantly greater in the post-training session than in the pre-training session in older adults (P = 0.001). However, perceptual training had no significant effect (P = 0.949) on the P300 component in young adults. Our results illustrate that cross-modal audio-visual perceptual training can lead to far-transfer effects in healthy older adults. These findings highlight the robust malleability of the aging brain, and further provide evidence for exploring interventional strategies to improve cognitive abilities in older adults.